CHANGES IN MOTOR SKILLS OF CHILDREN WHO TRAIN SPORTS SWIMMING AT THE INITIAL STAGE OF SCHOOL EDUCATION (IN ANNUAL TRAINING CYCLE) - Eider, Paul (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Introduction: This is an empirical article aiming at defining the changes of motor fitness in children practicing swimming at early stage of training in year-long training cycle. Proper selection of candidates to practice certain sports is a very complex process. One needs to select from the very large population of children, girls and boys, characterized by certain features, including somatic and motor features, which developed in a longstanding process of training, will lead them to become champions. The purpose of the research: The purpose of the research was to define the changes of motor fitness in girls’ practicing swimming at early stage of training in year-long training cycle. Material and Methods: The subjects to the research were 85 girls aged 7 (1st year of primary school), including 36 girls in swimming group and 49 girls in control group. 36 of them belonged to swimmers’ group- all girls were members of the Municipal Swimming Club in Szczecin. Control group consisted of 49 girls, who attended the same elementary schools. The examinations were carried out twice in the 2009-2010 academic year. The most reliable and accurate indirect test- EUROFIT Test Battery-was used. Results : The research revealed changes in both groups (Sw, C) in terms of all eight tests. Examination II proved statistically significant improvement of results in both groups (Sw, C) in comparison to Examination I. The dynamics of changes in general balance, flexibility, static force, functional force, running agility, was bigger in the girls who practiced swimming. As the speed of movement of upper limb, explosive force and thorax force are concerned; the differences of results in both examinations were similar in both groups (swimming group and control group). Progressive changes in motor fitness of the examined groups are a positive phenomenon in the development of child’s young organism. Conclusions: Swimming training significantly affected the dynamics of changes in motor fitness of girls at early stage of training, compared with control group (non-swimmers). Regular participation in sports activities (including swimming) positively affects the development of child’s motor (physical) fitness.